2013
DOI: 10.1161/circheartfailure.112.000146
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 and Cardiac Function in Survivors of Acute Myocardial Infarction

Abstract: Background-Galectin-3 is a biomarker associated with inflammation and fibrosis that predicts adverse outcome and relates to biomarkers of extracellular matrix turnover in patients with heart failure, particularly when left ventricular (LV) systolic function is preserved. Whether galectin-3 is related to LV remodeling after acute myocardial infarction is unknown. Methods and Results-Circulating galectin-3 and various extracellular matrix biomarkers were measured in 100 patients (age, 58.9±12.0 years; 77% men) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 35 publications
7
68
1
4
Order By: Relevance
“…Nevertheless, a clinical study by Weir et al did not confirm such association. They found no favorable effects of eplerenone on plasma Gal-3 levels over 24 weeks in patients after AMI [34]. A possible explanation for the conflicting findings of clinical and experimental studies lies in the observation that myocardial and serum concentrations of Gal-3 do not always correlate [60].…”
Section: Gal-3 As Target For Therapeutic Strategiesmentioning
confidence: 96%
See 2 more Smart Citations
“…Nevertheless, a clinical study by Weir et al did not confirm such association. They found no favorable effects of eplerenone on plasma Gal-3 levels over 24 weeks in patients after AMI [34]. A possible explanation for the conflicting findings of clinical and experimental studies lies in the observation that myocardial and serum concentrations of Gal-3 do not always correlate [60].…”
Section: Gal-3 As Target For Therapeutic Strategiesmentioning
confidence: 96%
“…Firstly, the most common finding among such investigations is that circulating Gal-3 levels are elevated in ACS/AMI, being released during the acute phase of AMI [31,[33][34][35][36][37][38][39]. Indeed, Gal-3 could be part of a survival mechanism of the injured myocardium to cope with the ischemic insult [14].…”
Section: Gal 3 In Acsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though, Weir et al had demonstrated that higher galectin-3 concentrations at baseline were significantly associated with lower LVEF at 24-week follow-up, although there was no significant relationship between galectin-3 and remodeling per se [32].…”
Section: Galectin-3mentioning
confidence: 99%
“…There has been intense interest in the setting of chronic heart failure in which galectin-3 has been shown to have an emerging role in the prediction, diagnosis and prognosis of this condition, presumably due to its pathogenic role in cardiac fibrosis [54][55][56][57][58][59][60][61][62]. Heart failure studies also demonstrated that galectin-3 levels were inversely correlated to GFR [57,[63][64][65].…”
Section: Galectin-3mentioning
confidence: 99%